The effect of localized density on housing prices in Singapore - FESSELMEYER, Eric (Institutional Knowledge at Singapore Management University, 2018)
This paper measures how localized residential density impacts housing prices in Singapore. Using exogenous variation in residential density, we find that an increase in density causes non-trivial decreases in property values: a 10% increase in density decreases price per square foot by between 1.3% and 2%. To the best of our knowledge, ours is the first paper to measure this effect.Further, we find that the negative effect of density is biggest in magnitude for low density apartment projects and the magnitude is decreasing in the density of the project, and that the negative effect of density is increasing in magnitude in the number of facilities in the project. In contrast, the effect of project density does not differ significantly by either project height or amount of open space.Our results contribute to the discussion on whether a denser urban form is a goal worth pursuing, suggesting that at least part of the benefits arising from externalities of high density are offset by the negative effects of localized density, which is manifested in households' willingness to pay a premium to live in low density apartment projects.